A field‐based disparity analysis of new 1, 2, 5‐oxadiazole derivatives endowed with antiproliferative activity. (14th May 2017) - Porta, Federica; Gelain, Arianna; Barlocco, Daniela; Ferri, Nicola; Marchianò, Silvia; Cappello, Valentina; Basile, Livia; Guccione, Salvatore; Meneghetti, Fiorella; Villa, Stefania
Abstract : A series of 1, 2, 5‐oxadiazoles were synthesized as new potential antiproliferative agents. The in vitro cytotoxic activity evaluation of title compounds through MTT assay revealed that some of them showed significant activity against the HCT‐116 cancer cell line. The field‐based disparity analysis provided indications about the electrostatic, hydrophobic, and shape features underlying the cytotoxicity, suggesting that increasing the negative electrostatic field on the heterocyclic core of the structure has positive effects on the activity. The structure–activity relationships (SAR) around a particular compound can be explained allowing for a structural rationale for the differences in activity. The SAR provided by this series of compounds can be exploited to carry out further lead optimization. Abstract : New 1, 2, 5‐oxadiazoles were synthesized as new potential antiproliferative agents. The field‐based disparity analysis highlighted the relevance of the negative electrostatic field on the heterocyclic core for activity. The SAR provided can be exploited to carry out further lead optimization.